Solutions of the Generalized Laguerre Differential Equation by Fractional Differintegral - Yilmazer, Resat; Karabulut, Serkan (Amer Inst Physics, 2018)
Fractional calculus techniques are used for the solutions of some classes of differential equations and fractional differential equations. One of the these tecniques is N-fractional calculus operator N method. We can obtain the fractional solutions differently from classical solutions by means of N method. In this study, we applied the Nmethod to the Laguerre equation.
7th International Eurasian Conference on Mathematical Sciences and Applications (IECMSA) -- AUG 28-31, 2018 -- Kyiv, UKRAINE
Keywords: Calculus Operator